Analisis SWOT Terhadap Strategi Pemasaran Ijarah Multijasa di BMT Mentari Bumi Panican, Purbalingga - Maulida, Indah Ilma; Fitriana, Novika Nur; Ismiati, Ismiati; Shafrani, Yoiz Shofwa (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the marketing strategy of the Multi-Service Ijarah product at BMT Mentari Bumi Panican, Purbalingga, using a SWOT analysis approach. The Multi-Service Ijarah is a service-based financing product used for non-asset needs such as education, healthcare, and other urgent expenses. Despite its great potential, the utilization rate remains low, accounting for only 19% of the total financing distributed. This research applies both descriptive quantitative and qualitative methods, through questionnaires and interviews with BMT's internal parties. The findings reveal that the main strengths of BMT lie in its fast and friendly service process and the provision of customer education regarding the contract. Its weaknesses include limited socialization and insufficient use of digital technology. Opportunities exist in fulfilling emergency financial needs, particularly for customers requiring flexible repayment options. However, threats arise from the public's lack of understanding of the Ijarah concept and competition from more recognized and accessible financial institutions and Islamic fintech platforms. Based on the identified SWOT factors, the study recommends strengthening promotional strategies, leveraging digital tools, and enhancing community education to improve competitiveness and market penetration of the Multi-Service Ijarah product. This research is expected to contribute to developing more effective marketing strategies in Islamic microfinance institutions.